Peculiarities of conduction Al2O3 irradiated with titanium ions in oxygen-contained medium; Взаимодействие излучений с твердым телом. ВИТТ-2005 - Kabyshev A. V. Alexander Vasilievich (2005, 2005)
В фонде НТБ ТПУ отсутствует